ASPARTATE TRANSAMINASE IN CHRONIC HEPATITIS B PATIENTS AT AWALBROS BATAM HOSPITAL - Suryani, Suryani; Dwika, Nubbeliano; Lestari, Rinda; Abrar, Mardhatillah (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2025)
Chronic hepatitis B (HBV) is a liver infection characterized by persistent replication of Hepatitis B virus (HBV). Viral load is a parameter often used to evaluate viral replication activity, while Alanine Transaminase (ALT) and Aspartate Transaminase (AST) often used as biomarkers to assess liver damage. Objective: This study aims to evaluate the correlation of HBV viral load to ALT and AST in patients with chronic hepatitis B at Awalbros Batam Hospital. Methods: This research used descriptive study by data collected from patients with chronic hepatitis B who had undergone testing assessments of HBV viral load, ALT and AST. Results: The results of this study is indicate a significant correlation of HBV viral load to ALT levels. Approximately 40% of patients showed elevated ALT levels in line with increasing HBV load, while AST increase was observed in only about 5% of patients. The stronger correlation was noted in ALT, likely due to its higher specificity to liver tissue compared to AST. Conclusion: Quantitative HBV load significantly influences ALT levels but has a less notable effect on AST levels. These findings support the role of ALT as a more reliable indicator of chronic HBV infection. The study also simplifies the clinical phases of infection into two main categories: active and inactive, based on presumed similarities in clinical patterns.